Problem Dualisme dalam Ontologi Filsafat Barat Modern dan Pascamodern - Ismail al-'Alam (Universitas Darussalam Gontor, 2017)
The problem of Dualism along the history of Western philosophy arise from full using of human ratio as the only source of knowledge, without refer to Holy Revelation in its original and final form. Ratio used in every speculation thinking about truth and reality. As an impact of these mode, according Heidegger’s argument in An Introduction to Metaphysics, the philosophers faced some inherent problems when they trying to explain what Being is. The problem is what Syed Muhammad Naquib al-Attas says as absolute-dichotomy on hakikat (an Indonesian word that refer to both Truth and Reality). Dialectically, the philosophers who emerge later always trying to solve this problem based on previously thought until now, when Postmodernism deconstruct subject, ratio, and Being. Even if their project is eliminate Being in philosophical reasoning, Postmodernists only shifting it without avoid the problem of Dualism.